A Bibliometric Analysis of the Research on Collaborative Writing in English as A Foreign Language (EFL) Context - Irpan Apandi Batubara (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
Collaborative writing is an emerging approach in teaching writing. This paper is aimed at using bibliometric analysis tools to examine works on collaborative writing in EFL context. The reviewed papers were Scopus database published between 2007 and 2023. The bibliometric analysis identified the following information: 1. Bibliometric analysis of publications on collaborative writing in EFL Context, 2) The citation analysis, and 3) the demographic analysis. The results showed that there were 86 publications for the search of “collaborative writing in EFL Context”. The most frequently used sources were Asia-Pacific Education Researcher, Asian EFL Journal, Computer Assisted Language Learning, Education and Information Technologies, and System. The annual production of the journals of collaborative writing in EFL context increases in the last four years. From only 10 publications in 2019, it becomes more than 20 in 2022. The top 5 authors are De Vleeschauwer J., Fathi J., McDonough K., Rahimi M., and Roy D.. The most relevant keywords can be categorized into affordance, collaborative problem-solving, group-oriented, gamification, computer-supported, etc. The international partnership involved authors from Asia, Europe, America, and Australia. The top university with publications of collaborative writing in EFL context were Islamic Azad University with four publications.